THE INFLUENCE OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT CENTURY PHARMACY, SOUTH JAKARTA - Irfan Rizka Akbar; Mitri Nelsi; Lily Setyawati Kristianti (International Journal Management and Economic, 2024)
The purpose of this research is to analyze and determine the influence of work discipline and work environment on employee performance at Century Pharmacy in South Jakarta, as well as to measure the extent of the influence of these two variables, both partially and simultaneously, on improving employee performance. The method used is quantitative analysis. The population in this study consists of all employees of Century Pharmacy in South Jakarta, totaling 63 individuals, while the sample used in this study was taken using a saturated sampling technique, where all members of the population were used as the sample. From this technique, a sample of 63 respondents was obtained. The data analysis used multiple regression analysis. The results of this study indicate that work discipline and work environment have a positive and significant effect on employee performance, with a regression equation showing a positive relationship between these variables. The coefficient of determination shows a significant simultaneous effect. The partial hypothesis test shows that work discipline has a positive and significant effect on employee performance. The work environment also has a positive and significant effect on employee performance. The hypothesis test shows that work discipline and work environment together have a positive effect on employee performance.